An evaluation of a behavioural support team for adults with a learning disability and behaviours that challenge from a multi‐agency perspective. (16th July 2015) - Christopher, Rose; Horsley, Sarah
Abstract : Accessible Summary: Dudley Behaviour Support Team aims to help make areas of life better for people with behaviours that challenge. It also aims to help their carers support them better. This project looked at whether the Behaviour Support Team is meeting guidelines set out by the government to ensure services are doing their job well. Staff who work with the Behaviour Support Team were asked to take part in the study by answering questions about how well the team does. This study found that the Behaviour Support Team is meeting the government guidelines to a high standard. Summary: The Dudley Behavioural Support Team (BST) was set up based on Positive Behavioural Support (PBS) principles to support individuals with behaviours that challenge. The Winterbourne Review emphasises the importance of developing high‐quality specialist community services and the Ensuring Quality Services (Local Government Association & NHS England, Ensuring quality services, London, 2014) document was released to guide the commissioning of such services. The document sets out standards and guidance for those supporting individuals with behaviour that challenges. This evaluation aimed to investigate whether the BST meets the guidance set out in Ensuring Quality Services from the perspective of other services. A questionnaire was developed to collect data from 19 staff members from services with experience of working with the BST, to address the points raised in Ensuring Quality Services. The quantitative results indicated that the BST are meeting the guidance to a high standard and qualitative data suggested this is achieved through a focus on joint working and a fluid, flexible approach. In conclusion, the BST appears to be a valuable resource from the perspective of services working with them to support individuals with behaviours that challenge.